Excitation energies of terthiophene and its dioxide derivative: A first-principles study - Della Sala, Fabio; Heinze, H.H.; Görling, Andreas (Chemical Physics Letters, 2001)
The excitation spectra of terthiophene and terthiophene-S,S-dioxide are investigated by time-dependent density-functional theory (TD-DFT) calculated data are compared with recent experimental results. The second singlet-triplet excitation energy (T) is calculated above the first singlet-singlet (S) one. In terthiophene-S,S-dioxide the formation of a bonding interaction in the lowest unoccupied molecular orbital decreases its kinetic energy and explains the red-shift of the excitation spectrum. The inter-system crossing (ISC) rate in terthiophene-S,S-dioxide is expected to be lower than in terthiophene due to the increased T-S energy gap, which is also found to not decrease with inter-ring torsion as in terthiophene. © 2001 Elsevier Science B.V.